2018
DOI: 10.1038/s41589-018-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme promiscuity drives branched-chain fatty acid synthesis in adipose tissues

Abstract: Summary Fatty acid synthase (FASN) predominantly generates straight-chain fatty acids using acetyl-CoA as the initiating substrate. However, monomethyl branched-chain fatty acids (mmBCFAs) are also present in mammals but thought to be primarily diet-derived. Here we demonstrate that mmBCFAs are de novo synthesized via mitochondrial BCAA catabolism, exported to the cytosol by adipose-specific expression of carnitine acetyltransferase (CrAT), and elongated by FASN. Brown fat exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
179
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 62 publications
15
179
0
Order By: Relevance
“…Accordingly, consumption of BCFAs and OCFAs may reduce the risk of cardiovascular disease [10,14] and metabolic disorders [15]. These fatty acids originate from ruminant fat and milk [16], but recent evidence suggests that both BCFAs and OCFAs can also be synthesized in mammalian adipocytes from branched-chain amino acids (BCAAs) [17][18][19]. Wallace et al [19] demonstrated that BCFAs were synthesized de novo in adipose tissue from BCAAs catabolized in mitochondria, and then exported by carnitine acetyltransferase to the cytosol, where they were elongated by fatty acid synthase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, consumption of BCFAs and OCFAs may reduce the risk of cardiovascular disease [10,14] and metabolic disorders [15]. These fatty acids originate from ruminant fat and milk [16], but recent evidence suggests that both BCFAs and OCFAs can also be synthesized in mammalian adipocytes from branched-chain amino acids (BCAAs) [17][18][19]. Wallace et al [19] demonstrated that BCFAs were synthesized de novo in adipose tissue from BCAAs catabolized in mitochondria, and then exported by carnitine acetyltransferase to the cytosol, where they were elongated by fatty acid synthase.…”
Section: Introductionmentioning
confidence: 99%
“…These fatty acids originate from ruminant fat and milk [16], but recent evidence suggests that both BCFAs and OCFAs can also be synthesized in mammalian adipocytes from branched-chain amino acids (BCAAs) [17][18][19]. Wallace et al [19] demonstrated that BCFAs were synthesized de novo in adipose tissue from BCAAs catabolized in mitochondria, and then exported by carnitine acetyltransferase to the cytosol, where they were elongated by fatty acid synthase. In a previous study, we identified several BCFAs and OCFAs in human serum, and demonstrated that patients with morbid obesity without any dietary or surgical treatment had significantly lower levels of iso-BCFAs than lean controls, but similar OCFA levels [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, adipose tissue is capable of substantial BCAA catabolism and can modulate circulating BCAA concentrations 36 . The rate of BCAA catabolism is particularly high in BAT and can regulate whole-body energy homeostasis [37][38][39] . BCAA catabolic enzymes are downregulated in adipose tissue both in obesity and in insulin resistence 38,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a strong predisposing factor for many diseases, including hypertension, high cholesterol, diabetes, and cardiovascular diseases. The thermogenic brown adipose tissue (BAT) not only dissipates chemical energy as heat to maintain body temperature and energy balance (Cannon and Nedergaard, 2004;Rosen and Spiegelman, 2014;Yang and Ruan, 2015), but also serves as a metabolic sink for glucose, fatty acids, and branched-chain amino acids to improve metabolic health Wallace et al, 2018;Maurer et al, 2019;Yoneshiro et al, 2019). Therefore, BAT has been increasingly acknowledged as a potential therapeutic target for obesity and related disorders.…”
Section: Introductionmentioning
confidence: 99%